Ultraviolet and / or x-ray excited fluorescent powder as well as preparation method and application thereof
By co-doping Sm3+/Cr3+ in the Zn3Ga2Ge2O10 matrix, ZGGO: 0.5% Cr3+, 5% Sm3+ phosphor was prepared, which solved the problem of the lack of near-infrared x-ray excitation of continuous luminescent materials in the prior art, achieved efficient near-infrared luminescence and long-term long-term luminescence, and enhanced the potential of x-ray imaging applications.
Patent Information
- Application Number
- CN202411811084.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The lack of development of near-infrared x-ray excitation continuous luminescent materials in the prior art, especially red x-ray excitation continuous luminescent materials, limiting the development of x-ray imaging applications. At the same time, the luminescent intensity of existing gallium germanate lasting luminescent materials is low and needs to be improved to expand the application field.
The high-temperature solid phase method combined with the gasless reduction and calcination method was used to co-dop Sm3+/Cr3+ in the Zn3Ga2Ge2O10 matrix, and the Sm3+/Cr3 doping concentration was optimized to improve the luminescence effect, and ZGGO: 0.5% Cr3+, 5% Sm3+ phosphor was prepared.
It has achieved bright near-infrared luminescence, long-lasting luminescence time, good biocompatibility and low toxicity, and improved the red luminescence intensity under x-ray excitation, and has potential applications in x-ray imaging and other fields.
Smart Images

Figure CN119639460A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoluminescent materials, and in particular relates to an ultraviolet and / or X-ray excited phosphor and a preparation method and application thereof. Background Art
[0002] Long-persistent phosphor is a unique photoluminescent material. After being excited by sunlight or artificial light, it emits visible light or infrared light, stores part of the light energy obtained, and continues to slowly release energy in the form of light after the excitation stops; the duration can be up to ten hours or even several days. At present, these materials have been widely used in night emergency command signals, electronic equipment displays, low-level lighting, home decoration and national defense and military applications. More research shows that they are expected to be widely used in cutting-edge scientific and technological fields such as information processing (such as latent fingerprint monitoring), new energy (such as new energy batteries and photocatalysis), life sciences (such as biomedical imaging), and new agricultural developments (such as plant light sources and agricultural films), thereby affecting future development.
[0003] In 1996, Matsuzawa et al. discovered the famous phosphor SrAl2O4:Eu 2+ ,Dy 3+ , a high-brightness green phosphor that can emit afterglow for several hours, has become an important milestone in the development of sustained luminescent materials. This discovery has attracted the attention of many researchers who are looking for phosphors that can emit different colors of light and produce longer afterglow. Currently available materials include CaAl2O4:Eu 2+ ,Nd 3+ (blue), SrAl2O4:Eu 2+ ,Dy 3+ (green) and other alkaline earth metal aluminate series persistent luminescent materials have the characteristics of high luminous efficiency, long persistent luminescence time, and high temperature resistance, but they also have disadvantages such as poor water resistance and few luminescent color varieties (lack of red and yellow light varieties). Visible light persistent luminescent phosphors have been successfully developed; in contrast, persistent luminescent phosphors that emit light in the near-infrared region are new materials, and their research and development are relatively lacking. Near-infrared light sources (780-2526nm) have the advantages of strong penetration, high resolution, and strong signal-to-noise ratio. They are widely used in biomedical testing and treatment, non-invasive testing, military reconnaissance, food testing and other fields. Therefore, near-infrared persistent luminescent phosphors have potential application prospects in these fields. In 2015, Tabane's research group reported lanthanide or transition metal doped near-infrared persistent phosphors, such as garnet and spinel, whose afterglow time after ultraviolet excitation ranged from a few minutes to a few hours.
[0004] Compared with persistent luminescent phosphors excited by ultraviolet and blue light, persistent luminescent phosphors excited by X-rays have unique applications such as X-ray imaging and detection. Recently, Liu et al. demonstrated that lanthanide-doped NaLuF4 phosphors can be used as flat-panel X-ray detectors, showing excellent 3D X-ray imaging capabilities.
[0005] In persistent luminescent phosphors, there are two types of active centers: trap centers and luminescent centers. Traps usually do not emit radiation, but store excitation energy, which is gradually released to the luminescent center due to heat or other physical stimulation. The luminescent center can emit radiation after being excited. Therefore, the emission wavelength of the persistent luminescent phosphor is mainly determined by the luminescent center, while the intensity and duration of the persistent luminescent phosphor are determined by the traps (such as trap type and distribution), which are usually related to lattice defects or co-dopants. Therefore, in the design of persistent near-infrared phosphors, near-infrared luminescent centers are required, which can generate and promote persistent luminescent traps. For near-infrared phosphors, the structural defects of the matrix are usually used as traps, and trivalent chromium ions Cr are doped 3+ As a luminescent center. Cr 3+ There are two emission modes: one is the 2Eg→4A2g transition mode at 700nm where spin is prohibited, and the other is the 4T2g→4A2g transition mode at 650-1600nm where spin is allowed. 3+ In the development of activated near-infrared crystals, gallium and gallium germanate have been shown to be suitable substrates. This is because in the distorted octahedral structure of gallate and gallium germanate, Cr 3+ Can replace Ga 3+ The position of gallate / germanate can be 3+ A suitable crystal field is generated around it, thus achieving near-infrared emission. 12 ,LiGa5O8,M3Ga2Ge4O 14 (M=Sr or Ca) and La3Ga5GeO 14 It is a suitable substrate. Gallium and gallium germanate doping will produce structural perturbations, dual defects, oxygen vacancies and co-doping, forming many deep wells; therefore, after stopping the excitation at room temperature, the afterglow time can last for several hours to several days. Pan et al. first reported a Cr 3+ Doped Zn3Ga2Ge2O 10 (ZGGO) near-infrared persistent phosphor with broadband emission in the range of 650-1100nm and an afterglow time of more than 360h. These authors suggested that near-infrared persistent materials could be used as markers for night vision monitoring and in vivo imaging applications. Subsequently, Shen et al. studied Cr 3+The influence of doping concentration on luminescence properties. Wu et al. studied the luminescence properties of samples sintered in different atmospheres and reported that the afterglow of samples sintered in air was longer than that in reducing atmosphere. Xu et al. 2+ Doping improved the emission spectrum and reported a 15-fold increase in emission intensity. Zhu et al. synthesized the same material using citrate anions by a hydrothermal method and obtained monodisperse, uniform spherical nanoparticles. When the nanoparticles were used as fluorescent probes for in vivo imaging, the near-infrared afterglow lasted for more than 120 minutes and the afterglow signal lasted for 60 minutes.
[0006] Although some progress has been made in the research of X-ray excited persistent luminescent materials, there are few reports on the development of near-infrared X-ray excited persistent luminescent materials (such as red X-ray excited persistent luminescent materials). Therefore, the development of X-ray excited red luminescent phosphors with bright intensity and long duration is of great significance for X-ray imaging applications. At the same time, the luminescence intensity of these gallium germanate persistent luminescent materials is generally low, and it is necessary to continue to find products with stronger luminescence intensity and better performance to expand their application in more fields. Summary of the invention
[0007] In order to solve the above technical problems, the present invention proposes a UV and / or X-ray excited phosphor and its preparation method and application. The present invention provides a series of persistent phosphors with near-infrared emission, wherein ZGGO:Cr 3+ ,Sm 3+ The present invention adopts a high temperature solid phase method combined with a gasless reduction calcination method to co-dope Sm in the ZGGO matrix. 3+ / Cr 3+ , found that Sm 3+ / Cr 3 The doping concentration will affect the luminescence effect. ZGGO: 0.5% Cr 3+ ,5%Sm 3+ (i.e. Cr 3+ and Sm 3+ Relative to the matrix Zn3Ga2Ge2O 10 The molar concentrations of the fluorescent materials are 0.5% and 5% respectively) and have the characteristics of bright near-infrared luminescence, long-lasting luminescence time, good biocompatibility, low toxicity, etc. The ultraviolet and / or X-ray excited fluorescent powder of the present invention can be used in lighting, night vision monitoring, solar energy utilization, in vivo biological imaging, X-ray imaging and plant light sources.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] One of the technical solutions of the present invention:
[0010] A UV and / or X-ray excited phosphor, the chemical formula of which is Zn3Ga2Ge2O 10 :xCr,ySm, where x=0.005, y=0~0.25, y is not 0.
[0011] Preferably, the chemical expression of the ultraviolet and / or x-ray excited phosphor is Zn3Ga2Ge2O 10 :xCr,ySm, x=0.005, y=0.001, 0.002, 0.005, 0.007, 0.05, 0.2 or 0.25. More preferably, x=0.005, y=0.05, i.e., the chemical expression of the ultraviolet and / or x-ray excited phosphor is Zn3Ga2Ge2O 10 :0.005Cr,0.05Sm, at this time Cr 3+ and Sm 3+ Relative to the matrix Zn3Ga2Ge2O 10 The molar concentrations are 0.5% and 5% respectively, so it can also be recorded as ZGGO: 0.5%Cr 3+ ,5%Sm 3 + .
[0012] The raw materials of the ultraviolet and / or X-ray excited phosphor include ZnO, Ga2O3, GeO2, Cr2O3 and Sm2O3.
[0013] The ultraviolet and / or x-ray excited phosphor of the present invention is a continuous luminescent material, whose luminescent spectrum is in the near infrared region, and the afterglow intensity is related to the trap density. The larger the appropriate trap density in the continuous luminescent material, the more electrons are captured, and the greater the afterglow luminescence intensity. 3+ The addition of Sm increases the sensitivity of the material trap. 3+ The doping of Sm enhances the residual luminescence intensity of the continuous luminescent material for two reasons: First, 3+ The doping of Sm increases the number of electron capture energy levels; secondly, 3+ The doping makes it easier for electrons to interact with Cr during the release process. 3+ The luminous centers combine, thereby increasing the sustained luminous intensity.
[0014] The second technical solution of the present invention:
[0015] The present invention also provides a method for preparing the ultraviolet and / or X-ray excited fluorescent powder, which is prepared by a high temperature solid phase method combined with a gasless reduction roasting method.
[0016] Preferably, the method for preparing the ultraviolet and / or x-ray excited phosphor comprises the following steps: accurately weighing the raw materials according to the elemental composition ratio, grinding to obtain a precursor, then pre-sintering the precursor, then sintering, cooling and then grinding to obtain the ultraviolet and / or x-ray excited phosphor.
[0017] The pre-sintering temperature is 1000° C. to 1200° C., and the time is 2 to 3 hours.
[0018] Preferably, the pre-sintering temperature is 1100° C. and the time is 2 hours.
[0019] The sintering temperature is 1300° C. and the sintering time is 3 hours.
[0020] The reasons for pre-sintering and then sintering in the process of preparing ultraviolet and / or x-ray excited phosphors in the present invention mainly include the following points: (1) Removal of impurities and volatiles: Pre-sintering can remove moisture, organic matter and other volatile impurities in the raw materials at a lower temperature, which helps to reduce gas release during sintering and avoid bubbles and cracks in the phosphor, thereby improving the quality and uniformity of the phosphor. (2) Promote raw material reaction: Pre-sintering helps the initial reaction and mixing between the raw materials, making the subsequent sintering process more uniform and complete, and helping to form a more uniform phosphor body. (3) Reduce sintering time: Through pre-sintering, the time required for subsequent high-temperature sintering can be reduced, because pre-sintering has promoted the combination and reaction of some raw materials, thereby saving energy and improving production efficiency. (4) Control of crystal form and particle size: Pre-sintering helps to control the crystal form and particle size of the phosphor, which is crucial to the luminescent performance of the phosphor. Through pre-sintering, excessive growth of grains during high-temperature sintering can be avoided, thereby obtaining more uniform and fine grains, which is very important for improving the luminescent efficiency and stability of the phosphor. (5) Improving sintering efficiency: Pre-sintering can improve sintering efficiency because it helps to achieve partial sintering at a lower temperature, making it easier to achieve complete sintering in the subsequent high-temperature sintering, thereby improving the overall performance of the phosphor.
[0021] The heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0022] The heating and cooling rates during pre-sintering and sintering have a significant impact on the performance of the phosphor, which is specifically manifested in the following aspects: (1) Crystal growth and phase change: The heating rate affects the crystal growth rate and phase change process. If the heating rate is too fast, it may cause incomplete crystal growth and form an amorphous or metastable phase, thereby affecting the luminescence performance of the phosphor. On the contrary, an appropriate heating rate can promote uniform crystal growth, help form a stable crystal structure, and improve the luminescence efficiency and stability of the phosphor. (2) Grain size and morphology: The heating and cooling rates affect the size and morphology of the grains. Rapid heating may cause uneven grain size, while slow heating helps uniform grain growth. The cooling rate is also important. Rapid cooling can inhibit further growth of the grains, maintain the small size of the grains, and help improve the luminescence intensity and color purity of the phosphor. (3) Luminescence performance: The cooling rate has a direct impact on the luminescence performance of the phosphor. For example, by changing the quenching temperature, the emission wavelength of the phosphor can be adjusted to meet different application requirements. Rapid cooling helps to maintain the integrity of the phosphor's crystal phase, reduce the formation of defects and impurity phases, and thus improve the luminescence efficiency. (4) Reduce defects and impurities: Appropriate cooling rate can reduce defects and impurities in phosphors and improve the luminescence performance of phosphors. (5) Improve the stability of phosphors: Appropriate heating and cooling rates help improve the thermal stability of phosphors and reduce chemical changes that may occur at high temperatures, thereby maintaining the long-term stability of phosphors.
[0023] The third technical solution of the present invention:
[0024] The present invention also provides the application of the ultraviolet and / or X-ray excited fluorescent powder in the fields of lighting, night vision monitoring, solar energy utilization, in vivo biological imaging for non-therapeutic purposes, X-ray imaging and plant light source.
[0025] Compared with the prior art, the present invention has the following advantages and technical effects:
[0026] The ultraviolet and / or x-ray excited phosphor of the present invention is a continuous luminescent material. In the present invention, Sm 3+ The addition of sensitizes the material traps and increases the number of electron capture energy levels, making it easier for electrons to interact with Cr during the release process. 3+ The luminescent center combines, so Sm 3+ The doping enhances the residual luminescence intensity of the persistent luminescent material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0028] Figure 1ZGO:Cr 3+ (i.e., TL3D x-ray excitation spectrum of Comparative Example 6);
[0029] Figure 2 ZGGO:Cr 3+ TL3D x-ray excitation spectrum of (i.e., Comparative Example 2);
[0030] Figure 3 ZGGO:Cr 3+ ,Eu 3+ TL3D x-ray excitation spectrum of (i.e., Comparative Example 3);
[0031] Figure 4 ZGGO:Cr 3+ ,Pr 3+ TL3D x-ray excitation spectrum of (i.e., Comparative Example 4);
[0032] Figure 5 ZGGO:Cr 3+ ,Sm 3+ TL3D x-ray excitation spectrum of (i.e., Example 5);
[0033] Figure 6 ZGGO:Cr 3+ ,Tb 3+ TL3D x-ray excitation spectrum of (i.e., Comparative Example 5);
[0034] Figure 7 ZGO:Cr 3+ 、ZGGO:Cr 3+ 、ZGGO:Cr 3+ ,Eu 3+ 、ZGGO:Cr 3+ ,Pr 3+ 、ZGGO:Cr 3+ ,Sm 3+ and ZGGO:Cr 3+ ,Tb 3+ TL intensity comparison;
[0035] Figure 8 ZGO:Cr 3+ XEOL spectrum;
[0036] Fig. 9 ZGGO:Cr 3+ XEOL spectrum;
[0037] Fig.10 ZGGO:Cr 3+ ,Eu 3+ XEOL spectrum;
[0038] Fig.11 ZGGO:Cr 3+ ,Pr 3+ XEOL spectrum;
[0039] Fig.12 ZGGO:Cr 3+ ,Sm 3+ XEOL spectrum;
[0040] Fig.13 ZGGO:Cr 3+ ,Tb 3+ XEOL spectrum;
[0041] Fig.14 ZGO:Cr 3+ 、ZGGO:Cr 3+ 、ZGGO:Cr 3+ ,Eu 3+ 、ZGGO:Cr 3+ ,Pr 3+ 、ZGGO:Cr 3+ ,Sm 3+ and ZGGO:Cr 3+ ,Tb 3+ XEOL intensity comparison;
[0042] Fig.15 Zn3Ga2Ge2O 10 、Zn3Ga2Ge2O 10 :Cr 3+ ,Sm 3+ , XRD spectra of ZnGa2O4, Zn2GeO4 and Sm2O3 phosphors;
[0043] Fig.16 ZGGO:Cr 3+ , Sm 3+ TEM (left) and high-resolution TEM (right) images;
[0044] Fig.17 ZGGO:Cr 3+ , Sm 3+ Excitation and emission spectra at room temperature;
[0045] Fig.18 For different Sm 3+ Excitation and emission spectra of samples with ion doping concentrations;
[0046] Fig.19 For different Sm 3+ The luminescence intensity of the sample with ion doping concentration;
[0047] Fig. 20 ZGGO:Cr after X-ray irradiation3+ , Sm 3+ TL3D spectrum (80-800K);
[0048] Fig.21 ZGGO:Cr at different temperatures (80~800K) 3+ ,Sm 3+ XEOL spectrum of phosphor;
[0049] Fig. 22 ZGGO:Cr 3+ ,Sm 3+ Bandwidth diagram of the phosphor XEOL spectrum;
[0050] Fig.23 After irradiation with 410nm blue light for 10min, ZGGO:Cr 3+ ,Sm 3+ 、ZGGO:Cr 3+ ,Eu 3+ 、ZGGO:Cr 3 + ,Pr 3+ 、ZGO:Cr 3+ and ZGGO:Cr 3+ ,Tb 3+ The continuous emission decay curve of the sample;
[0051] Fig.24 ZGGO:Cr after 10 seconds of X-ray excitation 3+ ,Sm 3+ 、ZGGO:Cr 3+ ,Eu 3+ 、ZGGO:Cr 3+ ,Pr 3+ 、ZGO:Cr 3+ and ZGGO:Cr 3+ ,Tb 3+ The near-infrared afterglow decay of the sample, monitoring the afterglow intensity (I) as a function of time (t) at 700 nm;
[0052] Fig.25 90SrβZGGO:Cr 3+ ,Sm 3+ TL glow curve and fitting curve;
[0053] Fig.26 ZGGO:Cr 3+ ,Sm 3+ The fitting curve of variable heating rate;
[0054] Fig. 27 ZGGO:Cr 3+ ,Sm 3+Dose response curves of
[0055] Fig.28 For different time periods, ZGGO:Cr 3+ ,Sm 3+ The integrated strength of the TL signal;
[0056] Fig.29 ZGGO:Cr at different decay times (0-3000s) 3+ ,Sm 3+ Thermoluminescence intensity;
[0057] Fig.30 When the decay time is 0s, ZGGO:Cr 3+ ,Sm 3+ TL kinetic fitting curve;
[0058] Fig.31 When the decay time is 60s, ZGGO:Cr 3+ ,Sm 3+ TL kinetic fitting curve;
[0059] Fig.32 When the decay time is 120s, ZGGO:Cr 3+ ,Sm 3+ TL kinetic fitting curve;
[0060] Fig.33 ZGGO:Cr when the decay time is 300s 3+ ,Sm 3+ TL kinetic fitting curve;
[0061] Fig.34 ZGGO:Cr when the decay time is 600s 3+ ,Sm 3+ TL kinetic fitting curve;
[0062] Fig.35 ZGGO:Cr when the decay time is 1200s 3+ ,Sm 3+ TL kinetic fitting curve;
[0063] Fig.36 ZGGO:Cr when the decay time is 3000s 3+ ,Sm 3+ TL kinetic fitting curve;
[0064] Fig.37 ZGGO:Cr 3+ ,Sm 3+ The relationship between the decay time and the TL peak intensity;
[0065] Fig.38 ZGGO:Cr 3+ ,Sm 3+ The relationship between the decay time and peak position;
[0066] Fig.39 ZGGO matrix and Cr 3+ Schematic diagram of the mechanism of continuous energy transfer between ions. DETAILED DESCRIPTION
[0067] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0068] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0069] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0070] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0071] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0072] Unless otherwise specified, the room temperature in the examples and comparative examples of the present invention is 25±2°C.
[0073] All raw materials used in the examples of the present invention are commercially available.
[0074] In some embodiments of the present invention, the phosphor is composed of ZnO (purity 99.99%), Ga2O3 (purity 99.99%), GeO2 (purity 99.99%), Cr2O3 (purity 99.99%), Sm2O3 (purity 99.99%), Pr6O 11 The raw materials are composed of Eu2O3 (purity is 99.99%), Eu2O3 (purity is 99.99%) and Tb4O7 (purity is 99.99%).
[0075] It should be pointed out that the matters not described in detail in the present invention are all conventional operating means in the field and are not the focus of the present invention. For example, specific methods such as screen printing, spraying, spin coating or drip coating are all completed using conventional methods.
[0076] The technical solution of the present invention is further illustrated by the following embodiments.
[0077] Preparation of Zn3Ga2Ge2O by high temperature solid phase reaction method 10 :xCr,ySm (x=0.005;y=0.001、0.002、0.005、0.007、0.05、0.2 or 0.25) Persistent phosphor:
[0078] Comparative Example 1 Preparation of Zn3Ga2Ge2O 10 :xCr,ySm(x=0,y=0)
[0079] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3 and 2 mol GeO2 were accurately weighed and ground in a mortar for 1 h to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours, and then the precursor was sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr,ySm(x=0,y=0), that is, Zn3Ga2Ge2O 10 , denoted as ZGGO, where the heating and cooling rates during pre-sintering and sintering were both 5°C / min.
[0080] Example 1 Preparation of Zn3Ga2Ge2O 10 :xCr,ySm(x=0.005,y=0.001)
[0081] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, 0.005 mol Cr2O3 and 0.001 mol Sm2O3 were accurately weighed and ground in a mortar for 1 h to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours, and then the precursor was sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr,ySm (x=0.005, y=0.001), that is, Zn3Ga2Ge2O 10 :0.005Cr,0.01Sm, recorded as ZGGO:0.5%Cr 3+ ,0.1%Sm 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0082] Example 2 Preparation of Zn3Ga2Ge2O 10 :xCr,ySm(x=0.005,y=0.002)
[0083] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, 0.005 mol Cr2O3 and 0.002 mol Sm2O3 were accurately weighed and ground in a mortar for 1 h to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours, and then the precursor was sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr,ySm (x=0.005, y=0.002), that is, Zn3Ga2Ge2O 10 :0.005Cr,0.002Sm, recorded as ZGGO:0.5%Cr 3+ ,0.2%Sm 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0084] Example 3 Preparation of Zn3Ga2Ge2O 10 :xCr,ySm(x=0.005,y=0.005)
[0085] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, 0.005 mol Cr2O3 and 0.005 mol Sm2O3 were accurately weighed and ground in a mortar for 1 h to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours, and then the precursor was sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr,ySm (x=0.005, y=0.005), that is, Zn3Ga2Ge2O 10 :0.005Cr,0.05Sm, recorded as ZGGO:0.5%Cr 3+ ,0.5%Sm 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0086] Example 4 Preparation of Zn3Ga2Ge2O 10 :xCr,ySm(x=0.005,y=0.007)
[0087] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, 0.005 mol Cr2O3 and 0.007 mol Sm2O3 were accurately weighed and ground in a mortar for 1 h to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours, and then the precursor was sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr,ySm (x=0.005, y=0.007), that is, Zn3Ga2Ge2O 10 :0.005Cr,0.007Sm, recorded as ZGGO:0.5%Cr 3+ ,0.7%Sm 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0088] Example 5 Preparation of Zn3Ga2Ge2O 10 :xCr,ySm(x=0.005,y=0.05)
[0089] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, 0.005 mol Cr2O3 and 0.05 mol Sm2O3 were accurately weighed and ground in a mortar for 1 h to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours, and then the precursor was sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr,ySm (x=0.005, y=0.05), that is, Zn3Ga2Ge2O 10 :0.005Cr,0.05Sm, recorded as ZGGO:0.5%Cr 3+ ,5%Sm 3+ or ZGGO:Cr 3+ ,Sm 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0090] Example 6 Preparation of Zn3Ga2Ge2O 10 :xCr,ySm(x=0.005,y=0.2)
[0091] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, 0.005 mol Cr2O3 and 0.2 mol Sm2O3 were accurately weighed and ground in a mortar for 1 h to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours, and then the precursor was sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr,ySm (x=0.005, y=0.2), that is, Zn3Ga2Ge2O 10 :0.005Cr,0.2Sm, recorded as ZGGO:0.5%Cr 3+ ,20%Sm 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0092] Example 7 Preparation of Zn3Ga2Ge2O 10 :xCr,ySm(x=0.005,y=0.25)
[0093] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, 0.005 mol Cr2O3 and 0.25 mol Sm2O3 were accurately weighed and ground in a mortar for 1 h to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours, and then the precursor was sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr,ySm (x=0.005, y=0.25), that is, Zn3Ga2Ge2O 10 :0.005Cr,0.25Sm, recorded as ZGGO:0.5%Cr 3+ ,25%Sm 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0094] Comparative Example 2 Preparation of Zn3Ga2Ge2O 10 :xCr(x=0.005)
[0095] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, and 0.005 mol Cr2O3 were accurately weighed and ground in a mortar for 1 h to obtain a precursor. The precursor was then pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours. The precursor was then sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr (x = 0.005), namely Zn3Ga2Ge2O 10 :0.005Cr, recorded as ZGGO:Cr 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0096] Comparative Example 3 Preparation of ZGGO:xCr 3+ ,yEu 3+ (x=0.005, y=0.05)
[0097] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, 0.005 mol Cr2O3 and 0.05 mol Eu2O3 were accurately weighed and ground in a mortar for 1 h to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours, and then the precursor was sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr,yEu (x=0.005, y=0.05), that is, Zn3Ga2Ge2O 10:0.005Cr,0.05Eu, recorded as ZGGO:Cr 3+ ,Eu 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0098] Comparative Example 4 Preparation of ZGGO:xCr 3+ ,yPr 3+ (x=0.005, y=0.05)
[0099] According to the element composition ratio, accurately weigh 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, 0.005 mol Cr2O3 and 0.05 mol Pr6O 11 , grind with a mortar for 1 h to obtain a precursor, then pre-sinter the precursor in a muffle furnace at 1100 ° C in an air atmosphere for 2 h, then sinter the precursor again at 1300 ° C for 3 h (air atmosphere), cool to room temperature, and grind to obtain Zn3Ga2Ge2O 10 :xCr,yPr (x=0.005, y=0.05), that is, Zn3Ga2Ge2O 10 :0.005Cr,0.05Pr, recorded as ZGGO:Cr 3+ ,Pr 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0100] Comparative Example 5 Preparation of ZGGO:xCr 3+ ,yTb 3+ (x=0.005, y=0.05)
[0101] According to the element composition ratio, 3 mol ZnO, 1 mol Ga2O3, 2 mol GeO2, 0.005 mol Cr2O3 and 0.05 mol Tb4O7 were accurately weighed and ground in a mortar for 1 h to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere at 1100 ° C in a muffle furnace for 2 hours, and then the precursor was sintered again at 1300 ° C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain Zn3Ga2Ge2O 10 :xCr,yTb (x=0.005, y=0.05), that is, Zn3Ga2Ge2O 10 :0.005Cr,0.05Tb, recorded as ZGGO:Cr 3+ ,Tb 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0102] Comparative Example 6 Preparation of ZGO:xCr 3+ (x=0.005)
[0103] 3 mol ZnO, 1 mol Ga2O3, and 0.005 mol Cr2O3 were accurately weighed according to the element composition ratio, and ground in a mortar for 1 hour to obtain a precursor, and then the precursor was pre-sintered in an air atmosphere in a muffle furnace at 1100°C for 2 hours, and then the precursor was sintered again at 1300°C for 3 hours (air atmosphere), cooled to room temperature, and ground to obtain ZnGa2O4:xCr (x=0.005), that is, ZnGa2O4:0.005Cr, recorded as ZGO:Cr 3+ , wherein the heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
[0104] By equipping 90 Srβ source and U-340 filter The TL / OSL-15-b / C reader system measures the TL / OSL luminescence curves of the phosphors prepared in the above examples and comparative examples. The temperature rise rate for TL measurement and preheating is set at 0.2-5°C / s. The radiation dose rate is 0.1 Gy / s. The sample is irradiated for 1-100000s, then linearly heated from room temperature to 500°C, and the TL signal is recorded.
[0105] The structures of the phosphors prepared in the above examples and comparative examples were analyzed by Rigaku Smart Lab SE x-ray diffractometer. The 2θ range of Cu radiation was 100-80°, and the speed was 50 / min. The PL spectrum of the phosphors was measured by Shanghai Prism F98 fluorescence spectrometer. A xenon lamp was used as the excitation light source. The TL3D and XEOL of the phosphors prepared in the above examples and comparative examples were measured by LTTL3DS spectrometer (Guangzhou Radiation Technology Co., Ltd.). These spectra supplement the wavelength-dependent information related to TL traps and defect structures. During the TL3D and XEOL spectrum measurements, the temperature of the sample (i.e., the phosphors prepared in the above examples and comparative examples) increased linearly at a rate of 1-5K / s. In order to measure the TL3D spectrum, the sample was placed in a sample tank and irradiated with x-rays. The TL3D spectrum of the sample was then measured. In order to measure the XEOL spectrum, the sample was also placed in a closed sample tank, evacuated (~1Pa) by a vacuum pump, and cooled to 80K with liquid nitrogen. Then, under x-ray irradiation, the XEOL spectrum of the sample at different temperatures was measured. The x-ray tube operates at 50 kV and 150 μA. The current is adjusted to keep the sample temperature between 80 and 800 K. The wavelength ranges from 200 to 850 nanometers.
[0106] TL3D and XEOL of different doped samples are shown in Figure 1-Figure 14 It can be seen that under the same dose of 50kV x-ray irradiation, ZGGO:Cr 3+ ,Sm 3+(i.e., ZGGO prepared in Example 5: 0.5% Cr 3+ ,5%Sm 3+ , the same below) than other samples (including the benchmark sample ZGGO:Cr 3+ ) has stronger X-ray-stimulated TL luminescence ( Figure 7 ). In addition, under the irradiation of 50kV x-ray with the same intensity, ZGGO:Cr 3+ ,Sm 3+ It also has stronger XEOL emission than other ZGGO-based phosphors ( Fig.14 ). This may be because Sm 3+ The excited state 4G5 / 2 and Cr 3+ The 4T2(4F) energy level matches that of Sm 3+ With Cr 3+ There is energy transfer between ions, which enhances the Cr 3+ The broadband emission of 4T2(4F)→4A2(4F). Therefore, ZGGO:Cr 3+ The luminescence intensity of the continuous luminescent material has been enhanced. 3+ ,Sm 3+ and GdAlO3:Cr 3+ ,Sm 3+ The results are similar. 3+ ,Sm 3+ The persistent luminescent material exhibits strong near-infrared luminescence at 700nm. Near-infrared light has strong penetrating ability and little damage to tissues, which is conducive to the application of this material in in vivo imaging. Therefore, ZGGO:Cr 3+ ,Sm 3+ Samples for subsequent testing.
[0107] Zn3Ga2Ge2O 10 、Zn3Ga2Ge2O 10 :Cr 3+ ,Sm 3+ The XRD spectra of ZnGa2O4, Zn2GeO4 and Sm2O3 phosphors are shown in Fig.15 , we can know that ZGGO:Cr 3+ ,Sm 3+ The XRD spectrum of ZGGO:Cr 3+ ,Sm 3+In the doped system, no impurity phase was observed. That is to say, there is no difference in the number and position of peaks in the spectra of doped and undoped samples. The strong peaks in the spectra of doped samples are in good consistency with the spectrum peaks of undoped samples, indicating that the prepared ZGGO has high purity, the doping impurities have little effect on the purity of the sample, and the crystal structure does not change with doping. ZGGO follows the ZnGa2O4 structure. ZGGO belongs to the cubic crystal system with a space group of Fd3m (space group number 227). The lattice parameters are The unit volume is Doping Cr in ZGGO matrix 3+ Later, Ga 3+ With Cr 3+ The ionic radius matches well, Cr 3+ There is substitution of Ga in the matrix lattice 3+ Compared with the XRD spectrum of Sm2O3, no characteristic diffraction peak of Sm2O3 was found in the XRD spectrum of the ZGGO sample, confirming that Sm ions are indeed doped into the lattice of the matrix.
[0108] ZGGO:Cr 3+ ,Sm 3+ TEM (left) and high-resolution TEM (right) images of Fig.16 , from ZGGO:Cr 3+ ,Sm 3+ The TEM image of ZGGO:Cr 3+ ,Sm 3+ It is non-spherical, with a size of about 500nm and different aspect ratios. 3+ ,Sm 3+ The high-resolution TEM image shows that the distance between the lattice fringes is about Corresponding to the spacing between the surfaces of the spinel gallium zinc germanate lattice (111).
[0109] ZGGO:Cr 3+ ,Sm 3+ The excitation and emission spectra at room temperature are shown in Fig.17 . From ZGGO:Cr 3+ ,Sm 3+ The excitation and emission spectra at room temperature show that due to the twisted Cr 3+ The ions undergo a 2E→4A2 transition, the ZGGO powder is excited at 410nm, and a near-infrared emission band is generated at 700nm. The excitation spectrum of the sample contains three main bands at 280nm, 410nm, and 558nm, and their positions and shapes are consistent with those of the previously reported ZGGO:Cr 3+(Z.Pan,YYLu,F.Liu,Sunlight-activated long-persistent luminescence in the near-infrared from Cr~ 3+ -dopedzinc gallogermanates, Nature Materials 11(1)(2012)58-63, https: / / doi.org / 10.1038 / nmat3173.) and ZGGO:Cr 3+ ,Pr 3+ (A.Abdukayum,JTChen,Q.Zhao,XPYan,Functional Near Infrared-Emitting Cr 3+ / Pr 3+ Co-Doped Zinc Gallogermanate Persistent Luminescent Nanoparticles with Superpersistent luminescence for inVivo Targeted Bioimaging, Journal of the American Chemical Society 135(38)(2013)14125-14133, https: / / doi.org / 10.1021 / ja404243v.). The excitation peak at 280nm may be the result of the interaction between the main excitation band of ZGGO and the charge transfer band of O-Cr. The 410nm (4A2→4T1(te2) transition) and 560nm (4A2→4T2) transitions are caused by Cr 3+ The self-activated luminescent ZGGO matrix shows a wide white emission band in the range of 350-660nm, and the maximum emission band is 505nm under 254nm excitation. This may be due to the electron-hole recombination between primary defects. 3+ / Sm 3+ After that, due to matrix emission and Cr 3+ There is an efficient non-radiative energy transfer between the absorption (4A2→4T1(te2) and 4A2→4T2 transitions), which makes the matrix emission and Cr 3+ There is a large spectral overlap between the absorption. This result is similar to the blue emission of ZnGa2O4 matrix and Cr 3+ These results confirm that there is energy transfer from the matrix to the Cr in the prepared ZGGO samples. 3+ energy transfer.
[0110] Under 410nm excitation, the material shows a broadened 2E-4A2 emission peak at 700nm, superimposed on a broad emission band from 650 to 800nm. The broadening of the 2E-4A2 emission may be caused by electron-phonon coupling, because Cr 3+ The phonon energy of the dopant is well matched with that of the ZGGO bulk, and the broadband emission may be due to some disordered Cr in the ZGGO system. 3+ ions due to the 2E-4A2 transition. 3+ Like phosphors, ZGGO:Cr 3+ ,Sm 3+ The excitation spectrum of the phosphor overlaps with the ultraviolet-visible range of solar radiation, so the phosphor can also be effectively activated by solar radiation.
[0111] The emission band increases sharply at 700nm and a peak appears at 717nm, which are caused by Cr 3+ The phonon satellite transitions of 2E→4A2 and 2E-4A2 are caused by ZGGO:Cr 3+ ,Sm 3+ The PL spectrum does not contain Sm 3+ The characteristic glow. Fig.18 For different Sm 3+ Excitation and emission spectra of samples with ion doping concentrations, Fig.19 For different Sm 3+ The luminescence intensity of the sample with ion doping concentration increases with the Sm 3+ As the ion concentration increases, the luminescence ability of Cr is significantly enhanced. 3+ and Sm 3+ When the concentrations of Cr and Cr are 0.5mol% and 5mol%, respectively, the 3+ ,0.1mol%Sm 3+ ) compared to the Sm. When this value is exceeded, the PL intensity decreases with increasing concentration due to concentration quenching. This is because in Sm 3+ Before the doping concentration reaches a certain value, increase Sm 3+ The doping concentration can be increased to Cr 3+ Transfer more energy and enhance luminescence; if Sm 3+ When the doping concentration reaches a certain value and continues to increase, Sm 3+ The interaction between ions will be enhanced, non-radiative energy transfer will occur, and the luminescence performance of the continuous luminescent material will be reduced. 3+ ,5%Sm 3+ Rare earth gallium germanate is the best matrix, and further exploration of doping Cr3+ Near-infrared continuous luminescence phosphor.
[0112] In order to further study ZGGO:Cr 3+ ,Sm 3+ The TL properties of the sample are shown in Figure 2. Under the condition of heating rate of 1K / s, the TL3D spectrum (80-800K) after 100Gy x-ray irradiation is as follows: Fig. 20 As shown. ZGGO:Cr 3+ ,Sm 3+ The phosphor has high TL sensitivity, with a peak luminescence temperature of 373K. The luminescence peak position is basically the same as that of PL, and there is obvious red light emission at 700nm. This is due to the Cr 3+ The 2E→4A2 transition of Sm was not found in TL3D. 3+ This indicates that in ZGGO:Cr 3+ ,Sm 3+ In the system, Cr 3+ The capture is the main thing.
[0113] Rare earth ions in the crystal produce emission bands when excited by X-rays. Since X-ray radiation can penetrate throughout matter, XEOL spectroscopy can provide quite detailed spectral data. Fig.21 XEOL spectra (80K-800K) obtained by irradiating ZGGO phosphor with x-rays (~0.1Gy / s) at different temperatures and a heating rate of 5K / s. An important emission band appears in the XEOL spectrum, and the red emission band is in the range of 650-750nm. The peaks of the XEOL spectrum are almost the same as those of the PL spectrum and the TL3D spectrum. Fig.21 It is shown that in the range of 100-500K, the luminous intensity of XEOL increases with the increase of temperature. However, when the luminous intensity is greater than 500K, the luminous intensity decreases. This is due to the ZGGO:Cr 3+ ,Sm 3+ The luminescence quenching phenomenon of continuous luminescent materials. Moreover, with the increase of temperature, the emission peak obviously shows a uniform thermal broadening phenomenon, and the peak position does not shift ( Fig. 22 ). This may be because the active ions are embedded in the crystal, and the surrounding lattice field has an effect on their energy level positions. Lattice vibrations cause the active ions to be affected by the changing lattice field, causing the energy levels to change within a certain range, making the spectral lines wider. As the temperature increases, the lattice vibrations become more intense and the width of the spectral lines increases. Since the effect of lattice vibrations on all active ions is essentially the same, this broadening is called uniform broadening. The excellent thermal stability of continuous luminescent materials is due to their ability to compensate for emission losses caused by non-radiative transitions. In BGO:Bi 3+Similar experimental results have been obtained in the study of continuous luminescent materials. The operating temperature of LED devices can reach 423K, and the operating temperature of LED chips usually weakens the fluorescence intensity of phosphors. 3+ ,Sm 3 + It has a luminescence enhancement effect at this temperature. For a certain radiation intensity, the luminescence intensity increases with increasing temperature. This phenomenon is caused by the conversion of energy stored in the internal defects of the phosphor into light radiation energy. Even at a thermodynamic temperature of about 100K, the sample shows obvious luminescence under X-ray excitation, indicating that low-temperature absorption of ambient infrared light will eliminate shallow traps in the material. This may be due to the tunneling effect. The above results show that the sample has good XEOL performance and high-temperature thermal stability, ZGGO:Cr 3+ ,Sm 3+ Persistent luminescent materials have the potential to be used as near-infrared LED luminescent materials.
[0114] Sm 3+ It is a positive trivalent lanthanide element with 4f electron configuration and high energy level. 3+ The trap density and depth of the persistent luminescent material can be varied to provide more efficient traps and optimize the ZGGO:Cr 3+ The sustained luminescence performance of sustained luminescence materials. ZGGO:Cr 3+ ,Sm 3+ In addition to strong and broad near-infrared luminescence, the phosphor also exhibits ultra-long near-infrared persistent luminescence after the excitation source is removed. Fig.23 After irradiation with 410nm blue light for 10min, ZGGO:Cr 3+ ,Sm 3+ 、ZGGO:Cr 3+ ,Eu 3+ 、ZGGO:Cr 3+ ,Pr 3+ 、ZGO:Cr 3+ and ZGGO:Cr 3+ ,Tb 3+ The continuous emission decay curve of the sample. The recorded data is a function of the continuous emission intensity (I) and time (t), and the recording time is 1000s. After 1000 seconds of continuous emission, the continuous emission intensity is still high. ZGGO:Cr 3+ ,Sm 3+ The afterglow is the longest, that is, the duration of the near-infrared afterglow exceeds that of ZGGO:Cr 3+ and ZGGO:Cr 3+ ,Pr 3 + .
[0115] In order to study the luminescence lifetime of the sample under X-ray excitation, the X-ray excitation at 700 nm was performed for 10 s and the ZGGO:Cr 3+ ,Sm 3+ 、ZGGO:Cr 3+ ,Eu 3+ 、ZGGO:Cr 3+ ,Pr 3+ 、ZGO:Cr 3+ and ZGGO:Cr 3+ ,Tb 3+ The continuous luminescence decay curve of the sample under 1000s is as follows Fig.24 After 1000s of continuous emission, ZGGO:Cr 3+ ,Sm 3+ The continuous luminescence intensity is still high. The X-ray excitation spectrum results show that ZGGO:Cr 3+ ,Sm 3+ Phosphors have strong X-ray-stimulated luminescence and sustained luminescence characteristics and have potential application value in the field of X-ray imaging.
[0116] Fig.25 90Srβ irradiated ZGGO:Cr 3+ ,Sm 3+ TL luminescence curve and fitting curve. The heating rate is 5℃ / s. ZGGO:Cr 3+ ,Sm 3+ The TL luminescence curve of the phosphor is in the range of 0-350℃, and there are two main TL luminescence peaks at 100℃ and 200℃. The luminescence curve cannot be fitted with a single kinetic peak, and at least three TL kinetic peaks are required to fit. These peaks correspond to the closures formed at different depths. The fitting results of each kinetic peak are shown in Table 1, and can all be described by the kinetic equation (1):
[0117]
[0118] In formula (1), n0 is the initial number of electrons captured in the sample; E is the electron capture activation energy (eV); S is the frequency factor; k is the Boltzmann constant; β is the heating rate of the sample (K / s); T is the absolute temperature (K); T0 is the temperature at t=t0 (K); and b is the motion order. Fig.25 The dynamic TL peaks are in good agreement with the experimental results. The fitting parameters of each dynamic peak are shown in Table 1. Peak 1 corresponds to the peak at 91°C, peak 2 corresponds to the peak at 190°C, and peak 3 corresponds to the peak at 205°C. The TL curve fitting results show that the activation energy (E) is in the range of 0.6 to 0.99 eV; the b value of the kinetic order (i.e., the motion order) is 1.5-2. The frequency factor (s) is 10 7 -10 10The initial electron concentration (n0) of the high-temperature peak is the largest, indicating that the trap concentration of the high-temperature peak is greater than the shallow trap concentration of the low-temperature peak.
[0119] Table 1 General kinetic fitting parameters of thermoluminescence peaks
[0120]
[0121] from Fig.25 It can be seen from the TL curve width and peak temperature that ZGGO:Cr 3+ ,Sm 3+ There are various traps of different depths in the material. Shallower traps are beneficial for PL luminescence at room temperature, while deeper traps can store energy and enable persistent luminescent materials to continue emitting light for a long time.
[0122] The ZGGO:Cr 3+ ,Sm 3+ The peak temperature changes. The experimental steps are as follows: select a single sample, preheat it from room temperature to 500℃ at a heating rate of 5℃ / s, and keep the temperature for 30s; then irradiate 1Gy with a 90Srβ radiation source, and measure and record the TL luminescence curve at a heating rate of 0.1℃ / s. Repeat the above steps, change the temperature rise rate of TL measurement to 0.2, 0.5, 1, 2, 5℃ / s, measure and record the TL luminescence curve. According to the kinetic theory of TL, the relationship between Tm and the heating rate β is:
[0123]
[0124] In formula (2), s is the frequency factor, E is the trap depth, k is the Boltzmann constant, and T m is the peak temperature (℃), and β is the heating rate (℃ / s). According to formula (2), several different heating rates are used, and the Tm value is recorded each time to generate a graph to obtain a straight line with a slope of E / k and a distance of ln(E / ks), and the values of E and s are obtained. According to the prediction of the Randall-Wilkins model, increasing the heating rate can move the highest peak temperature of the luminescence peak toward the high temperature direction. For the multi-speed method, the luminescence curve is measured at heating rates of 0.1, 0.2, 0.5, 1, 2, and 5℃ / s. The luminescence peak temperature of the high temperature peak is obtained by fitting the first-order kinetic function, and then the values of E and s are calculated according to the slope and intercept obtained from formula (2), as follows: Fig.26 The results are shown as follows: E = 0.93 eV, s = 1.32 × 10 9 , close to the energy level depth of peak 2.
[0125] The quantitative description of the TL dose response is based on the combined action model proposed by Luo et al. (D.L. Luo, K.N. Yu, C.X. Zhang, G.Z. Li, Thermoluminescence characteristics and dose responses in MgSO4:Dy,P and MgSO4:Dy,P,Cu phosphors, Journal of Physics D Applied Physics 32(23)(1999)3068 - 3074, https: / / doi.org / 10.1088 / 0022 - 3727 / 32 / 23 / 313). This model regards the TL dosimeter as composed of many identical small - volume elements called sensitive units. Assuming that the sensitive unit is a volume element centered on an electron trap, and its size depends on the concentration of the impurities contained. Assuming that the spatial distribution of secondary electrons generated by x - ray or γ - ray irradiating the medium is uniform, when the absorbed dose is D, the dose response F(D) satisfies the following formula:
[0126]
[0127] In Equation (3), D0 is the absorbed dose required for each sensitive unit to experience an ionization event on average, called the characteristic dose. R is the share of the single - action response, called the single - action factor. When 0 < R < 1 / 2, the response is linear - superlinear, and when 1 / 2 ≤ R ≤ 1, the response is linear - sublinear. ZGGO:Cr 3+ ,Sm 3+ The TL dose - response curve of the phosphor under 90Srβ source irradiation of 0.2 - 20000 Gy is as Fig. 27 shown. The area of the main TL peak is used as the ordinate, and the irradiation dose is used as the abscissa. The fitting results with formula (3) are D0 = 1583 Gy, R = 0.12. The results show that the dose - response linear range of ZGGO:Cr 3+ ,Sm 3+ is very wide. After irradiation of 10000 Gy, the sample signal is not completely saturated. The concentration of deep traps in the sample is very high.
[0128] The sample was exposed to 90Srβ rays of 10 Gy for fading study, and the exposed sample was placed in a lead tank in the dark for measurement. The sample was measured at different times, with the integrated intensity of the TL signal as the ordinate, and the results are as Fig.28 and Fig.29 shown. The signal attenuation at 1200 s is 27%, and the signal loss at 3000 s is about 33%.
[0129] Figure 30-Figure 36 For ZGGO:Sm 3+ ,Cr3+ Kinetic fitting curve of TL signal in. Peak 1 corresponds to the peak at 91°C, peak 2 corresponds to the peak at 190°C, and peak 3 corresponds to the peak at 205°C. Fig.37 Shows ZGGO:Sm 3+ ,Cr 3+ The functional relationship between the decay time of and the TL intensity of the three fitting peaks (peak 1-peak 3), Fig.38 ZGGO:Cr 3+ ,Sm 3+ The decay time and peak position relationship. The activation energy of peak 1 is 0.60eV (shallow well), and the activation energies of peaks 3 and 2 are 0.74eV and 0.99eV (deep well), respectively. The intensity of peaks 1 and 2 decreases exponentially with time, while the intensity of peak 3 remains essentially unchanged. This indicates that the signals of peaks 1 and 2 continue to decrease, while the signal of peak 3 continues to charge while decreasing.
[0130] Peak 1 moves toward higher temperature with decay time, while peaks 2-3 remain unchanged. The results show that peak 1 is not a single trap, but a continuous distribution of traps with similar energy level depths. Similarly, it can be inferred that peaks 2-3 also represent the same features.
[0131] ZGGO matrix and Cr 3+ The mechanism of continuous energy transfer between ions is as follows Fig.39 As shown. Under blue light excitation, the incident photon is absorbed by the ZGGO body and the electron rises from the valence band to the conduction band of ZGGO. The excited free electrons are then captured by primary defects through non-radiative relaxation. After the exposure is stopped, the recombination of electrons and holes released from natural defects causes broadband continuous luminescence. Since the three absorption bands of the host emission are closely related to Cr 3+ There is sufficient spectral overlap between the two so that the host energy is slowly and continuously transferred to the Cr by efficient nonradiative energy transfer. 3+ ions. Continuous energy transfer makes Cr 3+ The three-dimensional electrons rise from the ground state (4A2) to excited states of three different energy levels (4T1(te2), 4T1(t2e) and 4t2) at the same time. The excited electrons in the 4t1(te2) excited state are captured by the shallow trap (peak 1) through the conduction band and transferred to the deep trap (peaks 2-3) by non-radiative relaxation. After a period of time, due to the depletion of the shallow trap (peak 1), direct recombination through the conduction band may be ignored, and the trapped electrons in the deep trap (peak 2) will enter the shallower energy level (peak 3) by non-radiative relaxation, which also explains why the intensity of peak 3 does not decrease significantly with the decay time. Electrons in the shallower energy level (peak 3) can directly tunnel to the nearby ionized Cr 3+ ions and are trapped in the energy-matched Cr 3+This tunneling process does not require crossing the conduction band and occurs at a slow rate. This slow tunneling rate causes the light to persist for an extremely long time.
[0132] In addition, the afterglow intensity of the sustained luminescent material is related to the trap density. The larger the appropriate trap density in the sustained luminescent material, the more electrons are captured and the greater the afterglow intensity. 3+ The addition of Sm increases the sensitivity of the material trap. 3+ The doping of Sm enhances the residual luminescence intensity of the continuous luminescent material for two reasons: First, 3+ The doping of Sm increases the number of electron capture energy levels; secondly, 3+ The doping makes it easier for electrons to interact with Cr during the release process. 3+ The luminous centers combine, thereby increasing the sustained luminous intensity.
[0133] The presence of low-temperature afterglow at 80 K indicates that the emission of afterglow is related to tunneling. In addition, the activation of afterglow under 80 K blue light and X-ray irradiation indicates that excited electrons can be trapped under both low-energy and high-energy excitation.
[0134] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A UV and / or X-ray excited phosphor, characterized in that: Its chemical expression is Zn3Ga2Ge2O 10 :xCr,ySm, where x=0.005, y=0~0.25, y is not 0.
2. The ultraviolet and / or X-ray excited phosphor according to claim 1, characterized in that: x=0.005, y=0.001, 0.002, 0.005, 0.007, 0.05, 0.2 or 0.
25.
3. The ultraviolet and / or X-ray excited phosphor according to claim 1, characterized in that: The raw materials include ZnO, Ga2O3, GeO2, Cr2O3 and Sm2O3.
4. A method for preparing a UV and / or X-ray excited phosphor according to any one of claims 1 to 3, characterized in that: It is prepared by high temperature solid phase method combined with gasless reduction roasting method.
5. The method for preparing ultraviolet and / or X-ray excited phosphor according to claim 4, characterized in that: The method comprises the following steps: accurately weighing raw materials according to the element composition ratio, grinding to obtain a precursor, then pre-sintering the precursor, then sintering, and grinding after cooling to obtain the ultraviolet and / or X-ray excited phosphor.
6. The method for preparing ultraviolet and / or X-ray excited phosphor according to claim 5, characterized in that: The pre-sintering temperature is 1000° C. to 1200° C., and the time is 2 to 3 hours.
7. The method for preparing ultraviolet and / or X-ray excited phosphor according to claim 6, characterized in that: The pre-sintering temperature is 1100° C. and the time is 2 hours.
8. The method for preparing ultraviolet and / or X-ray excited phosphor according to claim 5, characterized in that: The sintering temperature is 1300° C. and the sintering time is 3 hours.
9. The method for preparing ultraviolet and / or X-ray excited phosphor according to claim 5, characterized in that: The heating and cooling rates during the pre-sintering and sintering processes are both 5°C / min.
10. Use of the ultraviolet and / or x-ray excited phosphor according to any one of claims 1 to 3 in the fields of lighting, night vision monitoring, solar energy utilization, in vivo biological imaging for non-therapeutic purposes, x-ray imaging and plant light sources.